DETERMINANTS OF UNDER-FIVE HEIGHT IN STUNTING PREVENTION EFFORTS IN TANJUNG JABUNG TIMUR, INDONESIA - Ena Sari, Rumita; Ibnu, Ismi Nurwaqiah; Herlambang, Herlambang (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background Stunting is the unsuccessful growth of children under five due to chronic malnutrition so that their height is not in accordance with their age. the prevalence of stunting based on the results of SSGI research in 2020, since 2013-2019 the decline in the prevalence of stunting in Jambi Province reached 7.8%. The weight of under-fives according to age range is one of the indicators in achieving optimal under-five growth. Objectives This study aims to analyze the determinants of body weight in under-two children in East Tanjung Jabung District. Methods Quantitative research with a cross-sectional design. The sample was 179 mothers and children under two selected by random sampling technique. The questionnaire has been tested for validity and reliability. Data were analyzed using the chi-square test. Results Maternal occupation (PR 4.507), family income (PR 4.507), breastfeeding pattern (PR 5.136), IMD practice (PR 4.825), breastfeeding (PR 4.305), smoking behavior in the house (PR 4.323), visits to the health fasilities (PR 5.247). Conclussion Based on the results of the study, maternal occupation, family income, breastfeeding pattern, IMD practice, breastfeeding exclusive, smoking behaviour in the house, and health facility visits were correlated with the height of infants. It is recommended that mothers and families can increase family economic income with the participation of the district government in helping the family economy. Mothers improve breastfeeding patterns and IMD practices, increasing visits to health facilities for monitoring children under two height, optimizing the role of cadres and also eliminating smoking behavior in the house. Keywords : Stunting, Children Under Two, Determinant